PEER INSTRUCTION (INSTRUÇÃO ENTRE PARES): UMA PROPOSTA METODOLÓGICA PARA O ENSINO E APRENDIZAGEM NA EDUCAÇÃO BÁSICA - RAMOS, TAÍS DE FÁTIMA (2023)
The traditional method of teaching is still strongly present in teachers' practice, everything is centered on the teacher, who passes on the content to students in the form of expository classes. Students are the role of passive spectator, all that remains is to memorize and reproduce knowledge. Normally, the teacher summarizes the content on the board, solves some questions as examples or models, then defines homework with the aim of fixing the content. With a rigid and extensive curriculum, assessments are standardized and linear and the recovery of subjects not understood is superficial. To try to reverse this situation, in recent years several methodologies have been studied and introduced into the practice of teachers, including Active Methodologies, which consider the student as the center of the teaching and learning process, taking an active role in the construction of knowledge, being the teacher is an important mediator of the process. Among the Active Methodologies, we have Peer Instruction, which will be the focus of this research and its guiding question is "What impacts occur on teaching and learning when we adopt the Active Peer Instruction Methodology in the teacher's practice in the classroom ?” From this question, the main objective will be “Analyze the observations made and the reflections produced by students and teachers in the development of activities through the Active Peer Instruction Methodology”, following the steps proposed by Mazur (2015). qualitative research, was applied to a class of the 1st year of full secondary education at a public school in the city of Guarapuava/Paraná, using Active Methodologies (Bacich & Moron, 2018) and the Peer Instruction methodology (Mazur, 2015) as theoretical references. The data collection instruments were carried out through observation of the activities carried out and recording in the logbook. Data analysis and interpretation was carried out as suggested by Bogdan and Biklen (1994), that is, a triangulation between the collected data, the theory and the researcher. After data collection and analysis, six categories were defined with the potential to answer the guiding question: Insecurity, commitment, time management, autonomy, teacher student relationship and indiscipline.